Influence of Direct-Fed Microbials on In-Vitro Dry Matter Digestibility, Rumen Fermentation Parameters and its Economics in Adult Sheep - Dangi, Rahul K; Shekh, Makbul A; Shah, Shailesh V; Agravat, Priyam H; Sherawat, Jitender; Singh, Prachand Pratap (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was aimed to find out the effect of direct fed microbials (DFM) on in-vitro dry matter digestibility (IVDMD), rumen fermentation parameters and its economics in 20 adult sheep. Based on the promising results from the laboratory-based in-vitro trials (49.55% IVDMD), the in-vivo study with a selected 2% level of DFM was further investigated. The sheep were arbitrarily split into two equal groups of ten each. The animals under T1 and T2 were fed compound concentrate mixture and roughage in conventional farm feeding as per ICAR (2013), additionally treatment group (T2) was supplemented with 2% DFM. The results for rumen fermentation pattern revealed that the average pH and TVFA values for T1 and T2 did not differ significantly. The experimental animals of DFM treatment group showed significantly (p<0.05) higher concentration of average total nitrogen (118.91 Vs. 100.71 mg/dL). The ammonia N, NPN concentration and TCA precipitable nitrogen concentration values were found to be non-significant (p>0.05) between two groups, while the ammonia N concentration was significantly (p<0.05) higher at 3 and 6 h post-feeding in both control and treatment group. The TCA precipitable nitrogen concentration values in rumen liquor neither differed significantly between groups nor at different time intervals post-feeding.